Socio-demographic Model of Gender Gap in Expected and Actual Wages in Estonia - Kristjan Vassil; Raul Eamets; Pille M\~otsmees (Institute for the Study of Labor (IZA), 2014)
Estonia ranks consistently on top of the list of countries with the largest gender pay gap. However, irrespective of abundant aggregate level evidence, little is known what motivates the gap at the individual level. In this paper we precisely address the issue of gender pay gap at the individual level. We examine how large is the gender pay gap in actual and expected wages and how it can be explained. We use a rich dataset from Estonian Labour Force Survey on actual wages, and the data from CV Keskus on people's wage expectations. Findings show that education and ethnicity are primary sources for gender based wage discrimination hinting at structural cleavages in Estonian society. Results have major policy implications for other multi-lingual countries with similar historical background.
Keywords: J16; J31; 330; gender wage gap; Estonia; expected wage gap; actual wage gap